The Mathematical Imagination : On the Origins and Promise of Critical Theory - Handelman, Matthew; Project Muse. (New York : Fordham University Press, 2019)
During the Weimar Republic, mathematics provided Gershom Scholem, Franz Rosenzweig, and Siegfried Kracauer - friends and forerunners of the Frankfurt School - with tools to navigate the crises of modernity. This study explores the histories of mathematics at the origin of critical theory and shows the enduring relevance of mathematics for critical thought.
Cover; The Mathematical Imagination; Title; Copyright; CONTENTS; Introduction: The Problem of Mathematics in Critical Theory; 1. The Trouble with Logical Positivism: Max Horkheimer, Theodor W. Adorno, and the Origins of Critical Theory; 2. The Philosophy of Mathematics: Privation and Representation in Gershom Scholem's Negative Aesthetics; 3. Infinitesimal Calculus: Subjectivity, Motion, and Franz Rosenzweig's Messianism; 4. Geometry: Projection and Space in Siegfried Kracauer's Aesthetics of Theory; Conclusion: Who's Afraid of Mathematics? Critical Theory in the Digital Age; Acknowledgments
Description based on print version record.
Keywords: Mathematics -- Philosophy; Jewish philosophy; Critical theory; SOCIAL SCIENCE -- Sociology -- General; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; critical theories (dialectical critiques); Philosophie juive -- 20e siecle; Mathematiques -- Philosophie; Theorie critique; Jewish philosophy -- 20th century; Mathematics -- Philosophy; Critical theory; Electronic books